A flow chart for the identification of Staphylococcus species (Journal of Veterinary Medicine and Animal Production, 2021)
The genus Staphylococcus contains some species that are considered among the important pathogens of humans and animals. A chart as guide for the identification of species and subspecies of this genus was designed 20 years ago by El Sanousi and Said based on the information present in the ninth edition of Bergy's Manual for Determinative Bacteriology (1994). As new species have been identified since then, update of the chart was necessary. The present chart represents a comprehensive revision and update of the first one. The key tests of the first chart were kept, but some amendments and modifications were made to include entries for all species and subspecies that are listed under the genus Staphylococcus in the second edition of Bergy's manual of systematic bacteriology (2009). The present chart allows for identification of 53 staphylococci with a few numbers of tests.
Keywords: Staphylococcus species; flow chart